Arrhythmic safety of hydroxychloroquine in COVID-19 patients from different clinical settings. Issue 12 (24th September 2020) - Gasperetti, Alessio; Biffi, Mauro; Duru, Firat; Schiavone, Marco; Ziacchi, Matteo; Mitacchione, Gianfranco; Lavalle, Carlo; Saguner, Ardan; Lanfranchi, Antonio; Casalini, Giacomo; Tocci, Marco; Fabbricatore, Davide; et al.
Abstract: Aims: The aim of the study was to describe ECG modifications and arrhythmic events in COVID-19 patients undergoing hydroxychloroquine (HCQ) therapy in different clinical settings. Methods and results: COVID-19 patients at seven institutions receiving HCQ therapy from whom a baseline and at least one ECG at 48+ h were available were enrolled in the study. QT/QTc prolongation, QT-associated and QT-independent arrhythmic events, arrhythmic mortality, and overall mortality during HCQ therapy were assessed. A total of 649 COVID-19 patients (61.9 ± 18.7 years, 46.1% males) were enrolled. HCQ therapy was administrated as a home therapy regimen in 126 (19.4%) patients, and as an in-hospital-treatment to 495 (76.3%) hospitalized and 28 (4.3%) intensive care unit (ICU) patients. At 36–72 and at 96+ h after the first HCQ dose, 358 and 404 ECGs were obtained, respectively. A significant QT/QTc interval prolongation was observed ( P < 0.001), but the magnitude of the increase was modest [+13 (9–16) ms]. Baseline QT/QTc length and presence of fever ( P = 0.001) at admission represented the most important determinants of QT/QTc prolongation. No arrhythmic-related deaths were reported. The overall major ventricular arrhythmia rate was low (1.1%), with all events found not to be related to QT or HCQ therapy at a centralized event evaluation. No differences in QT/QTc prolongation and QT-related arrhythmias were observed across different clinical settings, with non-QT-related arrhythmias being more common in the intensive care setting. Conclusion: HCQ administration is safe for a short-term treatment for patients with COVID-19 infection regardless of the clinical setting of delivery, causing only modest QTc prolongation and no directly attributable arrhythmic deaths.